Resources, support, and integration as potential barriers and facilitators to the implementation of blended therapy in the routine care of inpatients: a qualitative study - Gupta, Nikita; Leuba, Sophie; Seifritz, Erich; Berger, Thomas; Kawohl, Wolfram (Frontiers in Psychiatry, 2024)
While research on blended therapy (BT), i.e. the combination of face-to-face and digital treatment, has grown rapidly, integrating BT into routine practice remains limited, especially in inpatient settings. This study seeks to investigate the potential barriers healthcare providers and patients are confronted with in implementing BT to inpatients. Here, a retrospective, explorative qualitative research design was employed to gain insights into the experiences of healthcare professionals and inpatients in a real-world clinical setting. Specifically, we utilized semi-structured interviews to explore three key aspects: time resources, organizational support, and integration. A total of 11 therapists and 6 patients were interviewed. To our knowledge, this is one of the first studies to examine the implementation of blended therapy in the routine care of inpatients. We found that therapists emphasized several barriers including overwhelming workloads with insufficient time allocated for the work with the digital tools, inadequate time adjustments, a lack of ongoing training, and the necessity for a well-defined concept and setting of how to implement blended therapy. Interestingly, fewer barriers were reported by patients, who viewed the e-mental health platform as a valuable addition to their standard therapy. They also judged guidance and integration by their therapists as satisfactory and appreciated the adaptability offered in managing their workload in a flexible setting.